Análise térmica e econômica da produção de cal - Rosa, Flávia Sapper da (2019)
Mining companies have high yields, however, production processes employ low technology. Firewood is a frequently used energy source due to simple storage, low cost, high availability in the region and requires no processing. Therefore, the present work has the aim of analyzing the fuel consumption and possible improvements in the production process of lime in terms of use of raw material and costs. The furnace analyzed in this work was the continuous ravine type, which uses logs of firewood as fuel. In addition, this work aims to evaluate the temperature levels to which the operator is exposed, considering the norm NR 15. It was observed that, if the amount of fuel increases consequently the processing time decreases by up to 20%. This increases the amount of lime produced per batch thereby increasing profits for the company.